1981
DOI: 10.1093/carcin/2.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Promoting effect of Roussin's red identified in pickled vegetables from Linxian China

Abstract: Roussin's red (dimethylthiotetranitrosodiiron) has been identified as a non-alkylating N-nitroso compound present in pickled vegetables from Linxian, a high risk area for oesophageal cancer in China. In vitro experiments showed that Roussin's red had no significant mutagenic and transforming activities at the doses used, but it did enhance transformation in C3H/10TI/2 cells initiated with 3-methylcholanthrene (0.1 microgram/mI) and it decreased the number of sebaceous glands and increased the epidermal thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Extracts of pickled vegetables have shown mutagenic and transforming activities as well as promoting effects in vitro (Cheng et al, 1981), inducing hyperplasia and dysplasia in oesophageal epithelium and tumours in rodents (Yang, 1980). Heavy infestation of pickled vegetables with fungi is reported from Linxian (Yang, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracts of pickled vegetables have shown mutagenic and transforming activities as well as promoting effects in vitro (Cheng et al, 1981), inducing hyperplasia and dysplasia in oesophageal epithelium and tumours in rodents (Yang, 1980). Heavy infestation of pickled vegetables with fungi is reported from Linxian (Yang, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…This may facilitate the formation of N-nitroso compounds, which are strong oesophageal carcinogens in several animal models (Kamangar et al, 2009). Roussin red methyl ester, a non-alkylating nitroso compound with promoting effect in vitro, has been identified in pickled vegetables samples from Linxian in much higher concentrations than in samples from a low-incidence areas (Cheng et al, 1981;Zhang et al, 1983). Fumonisin mycotoxins have been shown to cause liver and kidney tumours in rodents (Kamangar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In high-risk areas of China, pickled food, particularly pickled vegetables, were eaten daily for 9 to 12 months a year and constituted an important part of the family diet (5). The traditional way of preparing pickled vegetables, packing moist vegetables in a jar for a few weeks or months, allows fermentation and growth of fungi and yeasts (5,7) and can potentially yield carcinogenic compounds such as N-nitroso compounds and mycotoxins (5,8,9). Indeed, a number of experimental and in vitro studies have shown mutagenicity and carcinogenicity of pickled vegetables (5,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Rousin red showed neither a mutagenic nor a transforming effect in Syrian hamster embryo cells. However, it did induce foci type 3 in CsH/lOT'/i cells initiated with 3-methylcholanthrene and did show a positive action in shortterm skin tests in mice; this led to a significant decrease in the number of sebaceous glands and a significant increase of epidermal thickness, as induced by 12-0-tetradecanoyl-phorbol-13-acetate (19). Therefore, Roussin red is one of the possible natural promoters present in pickled vegetables.…”
Section: Occurrence Of Nitroso Compounds In Fungi-contaminated Foods:mentioning
confidence: 98%